2010
DOI: 10.1007/s00347-010-2286-5
|View full text |Cite
|
Sign up to set email alerts
|

Reboundtonometrie und Applanationstonometrie während einer Narkoseuntersuchung beim kindlichen Glaukom

Abstract: The iCare rebound tonometer is useful during general anesthesia in cases of childhood glaucoma. It provides comparable IOP values to applanation tonometry with a tendency to record higher values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…13 In previous studies, the authors measured the IOP using an Icare rebound tonometer in pediatric glaucoma patients under general anesthesia and found that the IOP measurements were similar to those measured through Perkins applanation tonometry, which is highly correlated with Goldman applanation tonometry. 14,15 Furthermore, several previous studies have reported that the IOP could be measured using a rebound tonometer without complications in infants and children. 16…”
Section: Discussionmentioning
confidence: 99%
“…13 In previous studies, the authors measured the IOP using an Icare rebound tonometer in pediatric glaucoma patients under general anesthesia and found that the IOP measurements were similar to those measured through Perkins applanation tonometry, which is highly correlated with Goldman applanation tonometry. 14,15 Furthermore, several previous studies have reported that the IOP could be measured using a rebound tonometer without complications in infants and children. 16…”
Section: Discussionmentioning
confidence: 99%
“…The device automatically calculated an average value from 6 consecutive individual measurements [ 11 ]. Good comparability of rebound tonometry with Perkins applanation tonometry was found both in supine adults and in children under anesthesia [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%